Contested meaning of the nation-state through historical border narratives; A case study of the Batang Kanyau Iban, West Kalimantan - Pirous, Iwan Meulia (Wacana, Journal of the Humanities of Indonesia, 2011)
Nation as a cultural-psychological phenomenon is best understood in terms of how a sense of nationhood operates in order to construct social identities or a social imagination about the modern nation-state (Anderson 1983). The forging of nationalism as a national identity cannot be seen in isolation of the rise of modernization and industrialization (Gellner 1987). Although the nation appears to be a modern phenomenon, Smith (1991) stresses that every nation preserves its own past historical artefacts, narratives, and symbols for present-day needs. This model needs to be elaborated further as it is insufficient to understand how a sense of nationhood operates among borderlanders of a state. This paper relates the story of Kalimantan's Iban borderlanders who are officially registered as Indonesian subjects but live on the dividing line between two countries. This makes them appear to be ambiguous subjects who are torn between the two different historical timelines of British and Dutch colonial history (as well as postcolonial Malaysian-Indonesian history). They are marginalized in every aspect and are the forgotten subjects in the history of the broader picture of Indonesia's so-called nationalism project. The explanation is twofold. The first explains how identity is constructed as multi-layered historical narratives involving local and national cultures, and second, how transnational borderlanders give meaning to nation as narrative. The primary data for this article were collected in 2002 through a series of interviews in the village of Benua Sadap, an Iban settlement on the Batang Kanyau River, close to the West Kalimantan (Indonesia) and Sarawak (Malaysia) borderline.